Challenges facing regional live music venues: A case study of venues in Armidale, NSW. Issue 3 (December 2020) - Bennett, Cary
Abstract: This article draws from a wider research project undertaken in 2018 in Armidale, a small regional city in New South Wales (NSW) Australia, to explore the challenges commercial venues face in presenting and maintaining a regular live music programme. An analysis of the main themes suggests that the issues regional venues encounter are often qualitatively and/or quantitatively different from those facing their urban counterparts. This research found that regulatory issues, such as licensing, planning and noise, were not considered major impediments to regularly hosting live music. Rather, finding and accessing affordable quality bands in the numbers and styles needed to keep audiences coming to gigs, and getting audiences to regularly attend and spend money in the numbers needed to sustain the gigs, were identified as ongoing difficulties. Although venues in larger metropolitan cities are often confronted with similar problems, these are not the sort of issues that stand out in the research in this area. Rather the regulatory environment is emphasised. By drawing attention to the non-regulatory challenges regional venues face, important new avenues of research are opened up that will benefit live music scenes across Australia.